The Importance of High-Resolution Computed Tomography in the Early Diagnosis of Fibrotic Hypersensitivity Pneumonitis - D. А. Kuleshov; I. Е. Tyurin; М. V. Samsonova; А. L. Chernyaev (Вестник рентгенологии и радиологии)
Objective: to determine the high-resolution computed tomography (HRCT) signs and their combinations, suggesting the presence of fibrotic hypersensitivity pneumonitis (FHP).   Material and methods. The study included 52 patients with pathologically verified diagnosis of FHP who were examined according to the 2021 consensus criteria. All patients had lung HRCT no more than 4 months prior to lung biopsy. The analysis of the changes revealed during HRCT was carried out by qualitative and semi-quantitative methods. The presence of individual signs, the degree of their severity (as percentage relative to the volume of the entire lung tissue) and the features of distribution in the axial and longitudinal planes were taken into account. To search for significant combinations of HRCT signs, a correlation analysis was carried out.   Results. The most common HRCT signs in the examined group of FHP patients were reticular changes (96 %) and ground glass opacity (88 %). Most of the patients had signs that did not correspond to the picture of “typical FHP”, such as ground glass and emphysema. Relatively rare cases were centrilobular lesions (46.2 %) and mosaic attenuation (52 %), which are traditionally part of the “typical FHP” picture. In 22 cases (42.3 %) there were signs of emphysema, the presence of which significantly complicated the interpretation of HRCT data even in the cases of characteristic signs of FHP. Correlations of almost all HRCT signs were weak. The most common combinations of features were ground glass + reticular changes, emphysema + honeycombing, reticular changes + bronchiectasis. The combination of ground glass and reticular changes had a moderate correlation, but it has low specificity.   Conclusion. The HRCT picture of changes in the lungs among patients with a morphologically verified diagnosis of FHP has important features. A weak correlation between the signs does not allow to identify their combinations that can help in the early diagnosis of FHP with sufficient reliability.